Wettbewerb ohne Wettbewerb? Über die Bedeutung von Reformen im Bildungswesen für die Akzeptanz der Wettbewerbsidee - Uwe Dathe (OrdnungsPolitisches Portal (OPO), 2007)
This paper discusses a problem of the connexion between economic transformation and the present policy on education in the Ukraine and shows that without a systematic reconstruction of the educational system the transformation into a freemarket economy and a liberal political system will not succeed. The successful introduction and widespread public acceptance of the principle of competition is a necessary condition for an effective transformation in all transition countries. Although in the Ukraine a set of formal institutions has been introduced which should facilitate a free competition there is a lot of informal constraints which restrict the economic and political competition. Most of these constraints have historical causes, but above all they are products of the post-soviet development, especially of the policy on education. Both the official guidelines for the nation-building education (Ukrainian history, Ukrainian literature) and the practices at schools and universities create false uniformity and subordinate the individual to the national collective. The neglect of the ideas of individualism and social diversity is connected with the marginalization of the spirit of competition as a key to regulate economy and politics. In addition to the content of education we have a second source for the insufficient acceptance of the spirit of competition. The education system is highly corrupt. Informal practices instead of personal performances regulate access to the scare resources as good places at good universities or university degrees.
Keywords: 330; competition; spirit of competition; education; nation building; corruption